Si11Mn0/+ cluster is endohedral or exohedral: a proof by DFT calculation - Thanh Huong, Cao Thi; Thao Linh, Dao Thi; Minh Hue, Nguyen Thi; Cuong, Ngo Tuan (Vietnam Journal of Chemistry, 2017)
The geometries of Si11, Si11Mn+ and Si11Mn0 clusters have been determined by the method of density functional theory using B3P86/6-311+G(d) level of theory. The pure silicon clusters Si11have cage structure associating with a low spin state.Although the geometrical structure of the most stable isomer of Si11Mn+ cationic cluster is exohedral, the endohedral isomers have their calculated IR spectra fitting well with the experimental IRMPD spectra. The Si11Mn0 neutral cluster is found to be most stable in both exohedral and endohedral forms. The most stable isomers of manganese-doped silicon clusters Si11Mn0/+ possess high spin states and local magnetic moment of the Mn atom is reduced or even completely quenched when it is encapsulated inside the Si11 cage. Keywords. Silicon cluster doped manganese, density functional theory (DFT).